Analisis Determinasi Remitansi Dan Produk Domestik Regional Bruto Terhadap Tingkat Kesejahteraan Masyarakat Di Kabupaten Tulungagung - Adiva Joana Putri; Nafik Umurul Hadi (Departement of Mathematics Education, 2024)
This study aims to determine the influence of remittances and gross regional domestic product on the level of community welfare as seen from the value of public consumption in Tulungagung. This study is of a descriptive quantitative type, using multiple linear regression analysis and data used in the form of secondary data on remittances, ADHK GDP, and community consumption value in Tulungagung obtained from the Central Statistics Agency (BPS) Tulungagung. The results showed that the Remitan variable had a partially significant positive effect on the level of community welfare in Tulungagung district with a T-count value < T-table (6,480 > 1,672) and a significance of 0.000 < 0.05. The Gross Regional Domestic Product (GDP) variable has a significant positive effect on the community welfare in Tulungagung Regency with a T-count value > T-table (3.267 > 1,672) and a significant 0.000 < 0.05. Meanwhile, remittances and Gross Regional Domestic Product (GDP) simultaneously had a positive and significant effect on the level of community welfare in Tulungagung Regency with an F-count value > F-table (38,993 > 3,16) with a significant value of 0.000 < 0.05.